If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (1 + -1u)(2u + -7) = 0 Reorder the terms: (1 + -1u)(-7 + 2u) = 0 Multiply (1 + -1u) * (-7 + 2u) (1(-7 + 2u) + -1u * (-7 + 2u)) = 0 ((-7 * 1 + 2u * 1) + -1u * (-7 + 2u)) = 0 ((-7 + 2u) + -1u * (-7 + 2u)) = 0 (-7 + 2u + (-7 * -1u + 2u * -1u)) = 0 (-7 + 2u + (7u + -2u2)) = 0 Combine like terms: 2u + 7u = 9u (-7 + 9u + -2u2) = 0 Solving -7 + 9u + -2u2 = 0 Solving for variable 'u'. Factor a trinomial. (-7 + 2u)(1 + -1u) = 0Subproblem 1
Set the factor '(-7 + 2u)' equal to zero and attempt to solve: Simplifying -7 + 2u = 0 Solving -7 + 2u = 0 Move all terms containing u to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 2u = 0 + 7 Combine like terms: -7 + 7 = 0 0 + 2u = 0 + 7 2u = 0 + 7 Combine like terms: 0 + 7 = 7 2u = 7 Divide each side by '2'. u = 3.5 Simplifying u = 3.5Subproblem 2
Set the factor '(1 + -1u)' equal to zero and attempt to solve: Simplifying 1 + -1u = 0 Solving 1 + -1u = 0 Move all terms containing u to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1u = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1u = 0 + -1 -1u = 0 + -1 Combine like terms: 0 + -1 = -1 -1u = -1 Divide each side by '-1'. u = 1 Simplifying u = 1Solution
u = {3.5, 1}
| x-7=(2x-4) | | -9x+6y=72 | | 1-4j=2j | | Y=cos(3x) | | 8+2(3a-5)-(6a-8b*b)-4b*b= | | 8x+4y=-56 | | 5x^2+18x-8=0 | | 2.5x+15+0.5(x-4)=1.2x+2(0.5x-6) | | 4(2y+9)+7y= | | 7(x+2)=7x+2 | | (5x+3-2)(8-2x+1)= | | 9-.333g=13 | | 2x^2+9x=5 | | .25f=8-3 | | 3(4x-3)+2x=89 | | .25f+3=8 | | 3(4x+3)=68 | | 2(x+5)-10=8 | | 4x-20=7x+14 | | 15m-2(3+5m)= | | 15x^2-50y+35=0 | | 2-(8p-q)-7(p+6)+4q= | | -8x+x^2=-12 | | x^2-x-20=0 | | 7(p+3)=7b-4 | | f(11)=1/2(11)+5 | | 9(s+7)-(7s+m)-9m= | | f(11)=2(11)+5 | | 9(7x+8)+3(x+-10)= | | 7x+9=-11x+12 | | 7x+9and=-11x+12 | | -(9q+7)+3(2q-5)= |